Pengembangan Motif Batik Semarang untuk Penguatan Identitas Budaya Semarang - Titiek Suliyati; Dewi Yuliati (Jurnal Sejarah Citra Lekha, 2019)
At the beginning of its development, Semarang Batik motifs did not reflect the special character of batik that developed in other regions. At that time, Semarang Batik tended to show coastal motifs and many were influenced by the Dutch and Chinese.This article highlights the development of Semarang Batik which helped shape the identity of the city of Semarang, moreover with the acknowledgement of UNESCO in 2006 which also had an impact on the development of batik motifs in each region, including Semarang. The contemporer Semarang Batik motifs are in the form of city and cultural icons, such as Tugu Muda, Blenduk Church, Marabunta Building, Blekok Srondol, Wewe Gombel, Warak Ngendok, and even food motifs such as Lumpia, Tahu Gimbal, and so on. Historical method was used in this study, includingheuristics (source collection), criticism, interpretation, and writing facts. The results of this study can be concluded that, the present Semarang batik motif developing metamorphosis from traditional motifs to contemporary ones with more varied innovations.